CONFIGURATIONS OF ENGLISH THREE AND FOUR WORD ANATOMICAL TERMS AND THEIR LATIN EQUIVALENTS IN THE TEXTBOOK HUMAN ANATOMY (VOL. II) - Litevkienė, Nijolė; Briedytė, Jurgita (PROFESSIONAL STUDIES: Theory And Practice, 2023)
The extensive borrowing of words from Latin and Greek into English that began about 1500 AD continued for hundreds of years and continues to this day. The article analyses the variety of grammatical configurations of English and Latin multiword anatomical terms, their frequency, identity and differences in grammatical configurations. The textbook on human anatomy by M. Prives, V. Bushkovich, N. Lisenkov under the general editorship of prof. M. Prives reflects the data on anatomical science and offers a number of advantages over other textbook. Human Anatomy offers a progressive view descriptive, evolutionary, functional, and practical anatomy